The Pengaruh Kepemilikan Manajerial dan Free Cash Flow terhadap Nilai Perusahaan dengan Manajemen Laba sebagai Variabel Mediasi - Anthony Holly; Robert Jao; Ana Mardiana (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2022)
The type of this research is explanatory which aims to investigate the effect of managerial ownership and free cash flow on earnings management as well as managerial ownership, free cash flow and earnings management on firm value. In this research, agency theory and signaling theory are used to explain the relationship between variables.The population used in this study are non-financial companies listed on the Indonesia Stock Exchange with the 2016-2019 research period. This study uses a purposive sampling method. The results of this study indicate that managerial ownership has no effect on firm value, on the other hand, managerial ownership has a negative and significant effect on earnings management, while free cash flow has a positive and significant effect on firm value, on the contrary has a negative and significant effect on earnings management, besides earnings management has an effect on earnings management. positive and significant towards firm value. The sobel test results show that earnings management has a mediating role in the influence of managerial ownership on firm value, as well as free cash flow on firm value.